Lethal state: a history of the death penalty in North Carolina - Kotch, Seth (Justice, Power, and Politics, 2019)
The general sense of justice : lynching and the death penalty, 1880-1950 -- Without howling, without squirming : reinventing the death penalty in Jim Crow North Carolina, 1910-1936 -- I cannot allow this boy to be executed : the essential role of mercy, 1910-1949 -- Intelligent and civilized sentiments : activism, discretion, and the decline of the death penalty, 1941-1961 -- An emotional craving : the revival of the death penalty in North Carolina, 1961-1984